Saberes e práticas dos profissionais de saúde na atenção à pessoa com Diabetes Mellitus - Priscila Juceli Romanoski; Denise Maria Guerreiro Vieira da Silva; Julia Estela Willrich Böell; Maria Elena Echevarria Guanilo; Francieli Lohn da Rocha; Thais Silva Pereira Campos (Universidade Federal de Santa Maria, 2018)
Aim: to understand the knowledge and practices of health professionals in primary care for patients with diabetes mellitus and its complications. Method: descriptive qualitative, exploratory study conducted in five health centers in the city of Florianópolis, Santa Catarina. A semi-structured interview was conducted with 22 health professionals linked to the Family Health Strategy and to the Family Health Support Center between December 2014 and May 2015. The results were analyzed from the perspective of conventional content analysis. Results: the knowledge of professionals is formed through an integrated and humanized care, focusing on quality of life. Their care practices are distanced from such knowledge when the person already has the disease. Conclusions: although the participants manifest knowledge that converge with public policies, the clinical practice developed in the assistance of people with DM requires reflection and structuring in order to delay or avoid complications.